2015
DOI: 10.1002/pssb.201451662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorination on the TlBr band edges for improved room temperature radiation detectors

Abstract: Thallium bromide (TlBr) crystals subjected to hydrochloric acid (HCl) chemical treatments have been shown to advantageously affect device performance and longevity in TlBr‐based room temperature radiation detectors, yet the exact mechanisms of the improvements remain poorly understood. Here, we investigate the influence of several HCl chemical treatments on device‐grade TlBr and describe the changes in the composition and electronic structure of the surface. Composition analysis and depth profiles obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Research on the properties of TlBr has shown that ionic conduction contributes to deterioration of TlBr device performance at room temperature [30]. Methods have been developed involving crystal growth, surface processing, and electrode deposition that have enabled TlBr detectors to operate [31][32][33] for many months under continuous bias. Figure 12 shows photo peak channel and 241 Am pulse height spectra vs. time under 100 V bias for a 1 mm thick planar detector.…”
Section: Detector Stabilitymentioning
confidence: 99%
“…Research on the properties of TlBr has shown that ionic conduction contributes to deterioration of TlBr device performance at room temperature [30]. Methods have been developed involving crystal growth, surface processing, and electrode deposition that have enabled TlBr detectors to operate [31][32][33] for many months under continuous bias. Figure 12 shows photo peak channel and 241 Am pulse height spectra vs. time under 100 V bias for a 1 mm thick planar detector.…”
Section: Detector Stabilitymentioning
confidence: 99%
“…4,5 Reducing the reaction of the Br À ions with the electrode material has been the focus of a large body of TlBr research. Approaches include chemically treating the TlBr crystal to reduce defects at the surface, 6,7 altering the electronic structure at the interface, 8,9 and determining the optimal metallic electrode material. 10 The use of thallium contacts has shown promising results, with extended lifetimes of over 10 000 h being reported.…”
Section: Introductionmentioning
confidence: 99%